A Comprehensive Study of Routing Protocols in Cluster Based Wireless Sensor Networks - Rapolu, Praveen kumar; Srinu, B (International Journal of Computer Sciences and Engineering, 2025)
Nowadays Wireless Sensor Networks (WSN) plays vital role in different fields.WSN are more attractive because of their behavior in collecting various kinds of data from harsh environments. These Networks are more popular because these are buildup with less expensive nodes .Nodes in WSN collects the information and send to the base station or sink. Routing plays major role in improving the entire network life time by selecting optimized path. Routing is the process of reaching the destination from source node. Data can be sensed in two ways, those are flat and hierarchical .In flat routing each node in the network is given equal responsibilities. In case of hierarchical routing different nodes plays heterogonous tasks and organized into different clusters. Now in this paper a survey is taken on cluster based routing methods and comparing them with performance issues such as energy awareness, latency and scalability. Advantages and limitations of these methods are presented and conclude with open issues in cluster based routing in WSN